(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Disasters have become part of our lives, and they are becoming more severe every day with the increase in conflicts and pressures of life. The world has witnessed many natural and unnatural disasters and exceptional situations that have had a tangible impact on all political, social and economic levels, especially in developing countries that are most affected in terms of economic, material and human damage. Confronting and managing crises, including the occupation of Nineveh Governorate by ISIS terrorist gangs, requires an administration capable of employing appropriate efforts and capabilities and providing requirements to address their effects. The Martyrs Foundation’s procedures must also play an important role in all stages of the disaster. The research problem lies in what role does the Martyrs Foundation play according to INTOSAI Guide (5330) in managing the martyrs’ compensation file as a result of the attack by ISIS terrorist gangs. The research gained its importance from the importance of the existence of procedures for the Martyrs Foundation that managed the martyrs’ compensation file and takes into account its stages represented by prevention, mitigation, recovery and relief, national and international emergency response, rehabilitation, and reconstruction, in addition to helping auditors of international standards, including the INTOSAI Guide (5330), in completing audit procedures through the application of the relevant INTOSAI standards, in addition to the fact that the application guide 5330 is considered a powerful tool for improving disaster preparedness by providing direct guidance and instructions to the audit teams of the supreme audit institutions. The research seeks to identify the role played by the Martyrs Foundation according to the INTOSAI Guide (5330) in managing the martyrs’ compensation file as a result of the attack of the terrorist ISIS gangs. The research reached a set of conclusions, the most important of which is that evaluating the performance of the Martyrs Foundation’s procedures according to the INTOSAI Guide (5330) aims to find a strategy to confront crises and disasters that helps countries address the reality of the crisis with sound and thoughtful steps, through managing the martyrs’ compensation file and by adopting allocations before the crisis or disaster and setting all requirements to overcome the crisis and then evaluating what has been accomplished during the crisis or disaster. The research also presented a set of recommendations, the most prominent of which is compensating the families of actual martyrs by setting correct work controls and not allowing manipulation of this file.